Purification of olive mill waste: a circular economy model for the Mediterranean region - FEYZİOĞLU, AHMET; ERSOY, SEZGİN (My University, 2024)
When olive mill wastewater is given directly to nature without being treated, natural waters become coloured, aquatic life is adversely affected, surface and underground waters are polluted, bad odours occur, and soil quality deteriorates. For these reasons, waste water is not allowed to be poured into soil and water without being discharged. This problem has become a problem that needs to be solved for the Mediterranean countries. With this study, acid cracking and chemical treatability studies achieved the conversion of the physicochemical pretreatment process of olive black water to an automation system. With the applied processes, removal efficiencies of 85% for Chemical Oxygen Demand, 99% for suspended solids, 97% for oil grease and 92% for phenol were obtained. Since the mixing processes of the tanks in the chemical additions are long, the heating chamber in the acid cracking process is designed larger than the tanks. Thus, when there is a black water density in the system, the heating tank in this system can be used as a heating and resting tank in sudden densities in this system. This waste separation process includes producing raw materials, protecting natural resources, and increasing sustainability. In particular, separating the phenol material and making it usable have been essential gains. Keywords: life cycle practice; sustainability; olive processing; olive mill wastewater; Mediterranean countries
Keywords: life cycle practice; sustainability; olive processing; olive mill wastewater; Mediterranean countries